Prevalence and distribution of soil-borne zoonotic pathogens in Lahore district of Pakistan - Shabbir, Muhammad Z.; Jamil, Tariq; Muhammad, Khushi; Yaqub, Tahir; Bano, Asghari; MIrza, Ali I.; Bilal, Muhammad; Ahmad, Arfan; Ali, Muhammad A.; Ali, Asad A.; Chaudhary, Muhammad H.; Naeem, Muhammad; et al. (Frontiers in Microbiology, 2015)
A multidisciplinary collaborative project study was conducted to study the prevalence and distribution of soil-borne zoonotic pathogens in Lahore district of Pakistan and ascertain its Public Health Significance. Using a grid-based sampling strategy, soil samples (n=145) were collected from villages (n = 29, 5 samples/village) and examined for Bacillus anthracis, Burkholderia mallei/pseudomallei, Coxiella burnetii, Francisella tularensis, and Yersinia pestis using real time PCR assays. Chemical analysis of soil samples was also performed on these samples. The relationship between soil composition and absence or presence of the pathogen, and seven risk factors was ascertained. DNA of Bacillus anthracis (CapB), Burkholderia mallei, Coxiella burnetii and Francisella tularensis was detected in 9.6%, 1.4%, 4.8%, and 13.1% of soil samples, respectively. None of the samples were positive for protective antigen plasmid (CapA) of B. anthracis and Y. pestis. The prevalence of B. anthracis (CapB) was found to be associated with organic matter, Mg, Cu, Mn, Co, Cd, Na, Fe, Ca, and P. The prevalence of F. tularensis and C. burnetii was found to be associated with P and Cu, respectively. The odds of detecting DNA of F. tularensis was 2.7, 4.1, and 2.7 higher when soil sample sites were < 500 meters from vehicular traffic roads, < one kilometer from animal markets, and animal density > 1000 animals, respectively. While the odds of detecting DNA of C. burnetii was 32, 11.8, and 5.9 higher when soil sample sites were < 500 meters from vehicular traffic roads, presence of ground cover, and animal density of > 1000 animals, respectively. In conclusion, the findings of the study soil-borne pathogens are more likely to be detected in areas closer to roads with vehicular traffic along the interstate routes in Lahore where animals are held prior to auction, transport and slaughter.